Characterization of Schizosaccharomyces pombe Malate Permease by Expression in Saccharomyces cerevisiae - Camarasa, Carole (American Society for Microbiology, 2001)
In Saccharomyces cerevisiae, l-malic acid transport is not carrier mediated and is limited to slow, simple diffusion of the undissociated acid. Expression in S. cerevisiae of the MAE1 gene, encoding Schizosaccharomyces pombe malate permease, markedly increased l-malic acid uptake in this yeast. In this strain, at pH 3.5 (encountered in industrial processes), l-malic acid uptake involves Mae1p-mediated transport of the monoanionic form of the acid (apparent kinetic parameters: V(max) = 8.7 nmol/mg/min; K(m) = 1.6 mM) and some simple diffusion of the undissociated l-malic acid (K(d) = 0.057 min(−1)). As total l-malic acid transport involved only low levels of diffusion, the Mae1p permease was further characterized in the recombinant strain. l-Malic acid transport was reversible and accumulative and depended on both the transmembrane gradient of the monoanionic acid form and the ΔpH component of the proton motive force. Dicarboxylic acids with stearic occupation closely related to l-malic acid, such as maleic, oxaloacetic, malonic, succinic and fumaric acids, inhibited l-malic acid uptake, suggesting that these compounds use the same carrier. We found that increasing external pH directly inhibited malate uptake, resulting in a lower initial rate of uptake and a lower level of substrate accumulation. In S. pombe, proton movements, as shown by internal acidification, accompanied malate uptake, consistent with the proton/dicarboxylate mechanism previously proposed. Surprisingly, no proton fluxes were observed during Mae1p-mediated l-malic acid import in S. cerevisiae, and intracellular pH remained constant. This suggests that, in S. cerevisiae, either there is a proton counterflow or the Mae1p permease functions differently from a proton/dicarboxylate symport.